PENERAPAN SISTEM PENGELOLAAN SAMPAH ANORGANIK BERBASIS DIGITAL (TEMAN UBAH) DI KELURAHAN MARGASARI - Asep Winarto Nainggolan; Winna Miftahuljanah; Vira Luthfiati Az-Zahra; Verani Hartati (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
Garbage is one of the many issues confronting Indonesia. Waste emergency education is one type of solution planned to make residents aware of the importance of waste management. Waste emergency counseling activities are useful for every citizen to gain an understanding of the correct sorting of organic and inorganic waste. In the future, this understanding will become a source of information for every citizen managing and sorting their own household waste. The waste emergency that is happening in Indonesia is not primarily about residents who don't want to manage the waste, but about the fact that they have not been properly educated on how to manage the waste properly and correctly. Therefore, emergency education activities must be conveyed to many residents so that the volume of waste can be reduced over time. This counseling activity is described in this article, where the "TEMAN UBAH" team of Widyatama University students conducted a stretch of digital inorganic waste management for the residents of Margasari Village. The "TEMAN UBAH" team also aims to reduce the volume of inorganic waste in the Margasari Village environment.